Treasure of Jewelry and Clothing Accessories from the Late Middle Ages Discovered at Ordășei (Telenești District) - Vornic, Vlad; Matveev, Sergiu; Popovici, Sergiu; Peška, Jaroslav; Ursu, Ion; Dermenji, Lazari (Revista Arheologică, 2026)
In the autumn of 2024, on the plateau between the villages of Ordășei and Prodănești, a treasure consisting of 36 items – most of them made of silver, along with several bronze objects and two ceramic fragments – was discovered. The pieces were found scattered over an area of approximately 15×15 m, as a result of agricultural activity, near a Bronze Age barrow. The treasure includes jewelry and clothing accessories: filigree earrings with multifaceted settings, a multipartite earring with pendants, a truncated-conical pendant, an “S”-shaped belt clasp, numerous globular buttons of two types (small and large, some with a rattling core), as well as a fragment of a bronze ring. XRF analyses revealed the technological diversity of the items, most of them being made of silver with varying proportions of copper and tin, while two pieces belong to copper‑based alloys. Comparison with similar treasures from the Republic of Moldova and the Carpathian–Dniester region allowed the assemblage to be dated to the last decades of the 16th century through the end of the 17th century, most likely to its first half. The luxurious character of some pieces, as well as the presence of a rare belt clasp, suggests that the treasure belonged to a person of high social status. The study highlights the importance of medieval hoards for reconstructing the social, economic, and cultural contexts of the period.
Keywords: dle Ages; Ordășei; treasure; silver pieces; 16th-17th centuries